Students’ perceptions and experiences about the combined inductive-deductive approach in intermediate grammar class - Ismail, Dalia Abbas Ibrahim; Basthomi, Yazid; Karmina, Sari (Association for Scientific Computing Electrical and Engineering(ASCEE), 2023)
This research study investigates students’ perceptions and experiences about using the combined inductive-deductive approach in teaching English grammar in intermediate grammar class. The study employed a mixed methods design to answer the research questions. We used a questionnaire including four aspects according to ARCS Model to answer the first research question through examining the perceptions of 65 university students majoring English. Then five of 65 students were selected to be interviewed to explore their experiences on the combined inductive-deductive approach to answer the second research question. The results of the questionnaire and the interviews reveal that most students prefer the combined approach to teaching English grammar although they have positive perceptions towards the inductive or the deductive approach. The combined approach can provide students with better understanding of grammar and keep them involved and interactive in the learning process. Therefore, this current study suggests that further research should be conducted to investigate the effectiveness of the combined approach in the process of teaching grammar and teachers’ perceptions towards such approach.